A profile of illnesses prevailing in the secondary schools of rural communities of Bangladesh - Begum, Tanjima; Khanam, Parvin Akter; Rhaman, Mir Masudur; Sayeed, M Abu (IMC Journal of Medical Science, 2021)
Background and objectives: The childhood population in Bangladesh is 20% of the 166.5 million. The rural population comprises almost 70%. Approximately, Bangladesh has more than 23,500 high schools. There has been no published data on the profile of illness commonly observed among the high school children. The aims of the study were a) to determine a profile of common illness among the students of rural high schools; b) to assess the nutrition status related to socio-economic class and c) to find out the correlations between anthropometry and blood pressure and between anthropometry and blood glucose status. Methods: The study was conducted in purposively selected high schools in Santhia thana under the district of Pabna. Local leaders and the school teachers volunteered to communicate the study objectives and investigation details to the eligible students. The teachers prepared the list of participants. All the willing participants were advised to attend the investigation site in the morning in a fasting state. Each participant was interviewed. Socio-demographic and clinical history was taken. Investigations included anthropometry – height (ht), weight (wt), waist- and hip-circumference (waist, hip). Adiposity indices namely body mass index (BMI – wt in kg/ht in met. sq.), waist/hip ratio (WHR) and waist/ht ratio (WHtR) were calculated. Resting blood pressure was taken. Clinical examination (general and systemic) was done. Fasting blood glucose (FBG) was estimated using glucometer strip and blood grouping by test kit. Test kit was also used for detection of urinary protein. Results: From six schools, 1069 students (boys/girls = 392/677) of age 10 to 19 years participated in the study. The participants from middle class family were 52.7% and upper were 14.4%. Their mothers were mostly housewives (95.5%) and only 16% had academic education of ten years or more. The mean (± SD) values of BMI, WHR, WHtR and FBG were 18.2 (± 2.9), 0.81 (± 0.07), 0.43 (± 0.05) and 5.26 (± 0.45) mmol/L respectively. Adiposity was significantly higher in upper socio-economic class than the middle and lower class, though no differences were observed in blood pressure and blood glucose level. Of the illnesses, the most common were sinusitis (21.4%), tonsillitis (13.3%) and toothache plus dental caries (10.7%). Conclusions: The most common illnesses were sinusitis, tonsillitis and dental caries. Anthropometric measures indicated that adiposity was not uncommon in rural children. Though adiposity was found higher among the upper than the lower socio-economic class, blood pressure and blood glucose level showed no difference indicating equal risk of non-communicable diseases (NCDs) irrespective of socio-economic class. These findings envisage that the existing status of child health might lead to NCDs in adult life. We suggest adiposity, blood pressure and blood glucose status of a high school cohort may be prospectively followed for eventual future health events. Ibrahim Med. Coll. J. 2020; 14(2): 33-41